Early Involvement of Supplier in construction design phase and managing the framework agreement and financial criteria throughout the project cycle. - Abduhu, Ananya (Brac University, 2022)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.